2016
DOI: 10.1002/biof.1338
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin prevents mitochondrial dynamics disturbances in early 5/6 nephrectomy: Relation to oxidative stress and mitochondrial bioenergetics

Abstract: Five-sixths nephrectomy (5/6NX) is a widely used model to study the mechanisms leading to renal damage in chronic kidney disease (CKD). However, early alterations on renal function, mitochondrial dynamics, and oxidative stress have not been explored yet. Curcumin is an antioxidant that has shown nephroprotection in 5/6NX-induced renal damage. The aim of this study was to explore the effect of curcumin on early mitochondrial alterations induced by 5/6NX in rats. In isolated mitochondria, 5/6NX-induced hydrogen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
76
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(85 citation statements)
references
References 65 publications
5
76
0
Order By: Relevance
“…They are a class of highly shape‐changing organelles which continuously undergo fusion and fission. In physiological conditions, the shape of the mitochondria is normal, in the form of a rod or an ellipse, but their shape becomes swollen and ruptured to round under stress including various kidney diseases . The selective scavenging effect of autophagy on mitochondria is closely related to the biological activity of mitochondria .…”
Section: Resultsmentioning
confidence: 99%
“…They are a class of highly shape‐changing organelles which continuously undergo fusion and fission. In physiological conditions, the shape of the mitochondria is normal, in the form of a rod or an ellipse, but their shape becomes swollen and ruptured to round under stress including various kidney diseases . The selective scavenging effect of autophagy on mitochondria is closely related to the biological activity of mitochondria .…”
Section: Resultsmentioning
confidence: 99%
“…Two of the constructed A. thaliana TF expressing the AvSAMS1 gene (TF3 and TF6) and their parental non-TF line, Col-0, were treated with various stressors and then measured for root length. Results were shown as relative root growth (%) as described previously (Ezaki et al, 2000). Error bars indicate SD.…”
Section: Resultsmentioning
confidence: 99%
“…For A. thaliana , seeds were submerged in distilled water for 4 days at 4°C, grown in soil for approximately 3 week and then used for all experiments except for stress sensitivity tests. For stress sensitivity tests, seeds of A. thaliana were sterilized, submerged in sterilized water for 4 days at 4°C and then grown in hydroponic conditions with a fine nylon mesh net and a floating support in 1/6 MS medium (adjusted to pH 5.7; Ezaki et al, 2000) for 12 to 15 days. All plants were grown under fluorescent illumination (approximately 50 μEm −2 s −1 , 16 h of light and 8 h of darkness) at 25°C.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As already reported for CKD animal model and human studies [95,96], curcumin exhibits antioxidant properties, potentially useful in a prevention setting. In this regard, in a very recent animal study curcumin has been shown to be able to prevent early damage induced by 5/6 nephrectomy, not only ameliorating total antioxidant capacity, but also improving renal blood flow and acting in terms of mitochondrial function and bioenergetics [100]. But probably the most interesting systemic action of curcumin occurs at the intestinal level.…”
Section: Curcuminmentioning
confidence: 99%